TDP-43 extracted from frontotemporal lobar degeneration subject brains displays distinct aggregate assemblies and neurotoxic effects reflecting disease progression rates - Laferrière, Florent; Maniecka, Zuzanna; Pérez-Berlanga, Manuela; Hruska-Plochan, Marian; Gilhespy, Larissa; Hock, Eva-Maria; Wagner, Ulrich; Afroz, Tariq; Boersema, Paul J; Barmettler, Gery; Foti, Sandrine C; Asi, Yasmine T; et al. (Nature neuroscience, 2019)
Accumulation of abnormally phosphorylated TDP-43 (pTDP-43) is the main pathology in affected neurons of people with amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). Morphological diversity and neuroanatomical distribution of pTDP-43 accumulations allowed classification of FTLD cases into at least four subtypes, which are correlated with clinical presentations and genetic causes. To understand the molecular basis of this heterogeneity, we developed SarkoSpin, a new method for biochemical isolation of pathological TDP-43. By combining SarkoSpin with mass spectrometry, we revealed proteins beyond TDP-43 that become abnormally insoluble in a disease subtype-specific manner. We show that pTDP-43 extracted from brain forms stable assemblies of distinct densities and morphologies that are associated with disease subtypes. Importantly, biochemically extracted pTDP-43 assemblies showed differential neurotoxicity and seeding that were correlated with disease duration of FTLD subjects. Our data are consistent with the notion that disease heterogeneity could originate from alternate pathological TDP-43 conformations, which are reminiscent of prion strains.